Evaluation of the Incidence of Chorionic Villus Sampling Complications at 10-13 Weeks of Gestation for Early Diagnosis of Major Thalassemia - R Monzavi Sani (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Early diagnosis of thalassemia with chorionic villus sampling (CVS) has an important role in fetal evaluation. Because of increasing risk of fetal loss and other probable risks, it seems that information about the incidence of complications of this method in the mother and the fetus is invaluable. Therefore this study was performed to evaluate the incidence of complications of chorionic villus sampling in Sistan and Baluchestan province, Iran.METHODS: This cross sectional study was performed on 137 pregnant women (gestational age of 10-13 weeks) who referred to CVS center of Zahedan University of medical sciences, Zahedan, Iran. Transabdominal chorionic villus sampling was performed with sonographic guide. Samplings were sent to genetic laboratory. Immediately after sampling, the control sonography was performed for detecting the placental hemorrhage at the sampling site, subchorionic hematoma and fetal heart rate. The pregnant woman was discharged after 2 hours rest. Also, the final evaluation was performed on neonates to detect any defects.FINDINGS: The most common early complication of CVS was subchorionic hematomain in 9 (6.5%), that in one of these cases placental abruption was observed and abortion occurred finally. Fetal loss rate was 0.7% (1 case) and no defects were found in neonatal follow up. CONCLUSION: The results of this study show that chorionic villus sampling could be dangerous and it should be done carefully and if CVS is performed after 10 weeks of gestation, it does not increase the risk of fetal anomalies.